Multi-focus Image Fusion Based on Region Segmentation - Yuan Jia-zheng; Li Qing; Sun Bo-xuan (Institute of Advanced Engineering and Science, 2013)
We proposed a new image fusion algorithm based on region segmentation. The algorithm divided the adjacent region from the image through the edge detection, then using wavelet transform with different high-frequency fusion method in each sub-region, to retain the edge information of the source image. The experimental results showed that the image fusion algorithm based on region segmentation can overcome the drawbacks of single segmentation rule and processing in specific part, and the effect is better than the traditional wavelet-based image fusion algorithm. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3521